1996
DOI: 10.1525/aa.1996.98.3.02a00060
|View full text |Cite
|
Sign up to set email alerts
|

Korean Shamans and the Spirits of Capitalism

Abstract: S Recent studies have taught us that “religion” is not a fixed category but an instrument of popular consciousness. While the studies' subjects have often been victims of colonialism and capitalist exploitation, cultural production through magical means need not be restricted to a society's most oppressed elements. Counter to the expectations of Max Weber, for whom capitalism marched to the drumbeat of “rationalization,” many of the clients who patronize the shaman shrines of Seoul, Republic of Korea, are enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…8 Recent Sámi shamanism is gendered: their shamans were male, often with female assistants. Elsewhere, shamanism often tends to be gendered; for instance, most San shamans are male (Katz, 1981) and Korean shamans are mainly female (Kendall, 1996). We speculate about a possible link between the mostly male gendering of Sámi shamans and the mostly female gendering of seiDworkers of the sagas, if the female seiDworker came to be trained as 'assistant', as Sá mi females were.…”
Section: Jochens Says Thatmentioning
confidence: 93%
“…8 Recent Sámi shamanism is gendered: their shamans were male, often with female assistants. Elsewhere, shamanism often tends to be gendered; for instance, most San shamans are male (Katz, 1981) and Korean shamans are mainly female (Kendall, 1996). We speculate about a possible link between the mostly male gendering of Sámi shamans and the mostly female gendering of seiDworkers of the sagas, if the female seiDworker came to be trained as 'assistant', as Sá mi females were.…”
Section: Jochens Says Thatmentioning
confidence: 93%
“…Idleness was condemned while organization and discipline became marks of salvation. In Korea puritanical discipline reconciled capitalist accumulation with moral virtue and thereby circumvented the Neo-Confucian 'contempt for commerce' (see Eckert et al, 1990: 225;Kendall, 1996: 520).…”
Section: Puritanical Origins Of Korean Protestantism and The Communitmentioning
confidence: 99%
“…Shamanism's concern with wealth, however, is itself a product of the modern Korean economy. From her work with shamans in Seoul, Laurell Kendall (1996) found that shamans commonly complained that it was only now that kut (shamanic rituals) were held in the hope of riches.…”
Section: Miracles Of the Mundane: Health And Wealth As Indexes Of Mormentioning
confidence: 99%
“…Whether called shamanism, neoshamanism, urban shamanism, shamanic, White Spirit Teaching, Nature worship, animism, purification or something else entirely, rekindled religiosity links indigenous Siberian peoples with combined spiritual and ethnonational revitalisation trends throughout the world (cf. Balzer, 1997;Niezen, 2000;Humphrey, 1999;Kendall, 1996;Lester, 2002).…”
Section: How Does It Add Up? Why Should It?mentioning
confidence: 99%